1,2-dihydroxynaphthalene as Biomonitoring of Occupational Exposure to Naphthalene - Erwanda Desire Budiman; Muhammad Ilyas (The Indonesian Journal of Occupational Safety and Health, 2022)
Introduction: Naphthalene is a chemical exposure found in various industries, including in the manufacture of phthalic anhydride, synthetic resins, lubricants, mothballs, and used as fuel additives. The exposure to naphthalene in humans has several detrimental health effects such as hemolytic anemia, kidney and liver disorders. Therefore, biological monitoring is needed as a health surveillance of naphthalene exposure. Generally, the biomonitoring examination carried out for this is naphthol in the blood. However, 1,2-dihydroxynaphthalene (1,2-DHN) is also known to be another major metabolite. Therefore, this literature review aims to determine whether 1,2-DHN can also be a reliable biomonitoring test on occupational exposure to naphthalene. Methods: PubMed, Proquest, and Google Scholar were used to conduct article searches. The articles were chosen based on predetermined inclusion and exclusion criteria. The selected articles were then critically appraised. Results: Four cross-sectional articles examining 1,2-DHN in the urine of naphthalene-exposed workers were selected and reviewed. There was a similar result from all selected articles that elevated levels of 1,2-DHN in the urine, indicating workplace exposure to naphthalene. Moreover, apart from having a strong correlation with 1- and 2-naphthol, 1,2-DHN also has a high sensitivity compared to these established metabolites. Conclusion: Based on the articles obtained, 1,2-DHN can be a reliable biological monitoring for workers exposed to naphthalene. However, further research is still needed on other industries exposed to naphthalene and is needed to ascertain the correlation between external and internal exposure to naphthalene.